2009
DOI: 10.1177/1534735408327995
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effects of HESA-A in Patients With Metastatic Colon Cancer

Abstract: Background: HESA-A is a natural biological compound of herbal—marine origin. The aim of this study was to investigate the therapeutic effects of HESA-A in patients with metastatic colon cancer. Methods: Fifty consecutive patients with end-stage colon cancer and liver metastasis at the Cancer Research Center of Tehran University of Medical Sciences were studied. Patients received HESA-A 50 mg/kg/d orally in 2 to 3 divided doses for 6 months. The patients were assessed at the start and end of the 1st, 2nd, 4th, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In addition, the survival of patients until the end of the study, despite a predication of mean survival rate of 1 month, was noteworthy. 23 Ahmadi carried out a study in 2010 on patients with metastatic cancers, who had received HESA-A, and reported that this medicine can improve the quality of life and survival rate in such patients. 24 It is obvious that more animal studies are necessary with different doses in order to determine the optimal dose to prevent oral cancers, paving the way for human studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the survival of patients until the end of the study, despite a predication of mean survival rate of 1 month, was noteworthy. 23 Ahmadi carried out a study in 2010 on patients with metastatic cancers, who had received HESA-A, and reported that this medicine can improve the quality of life and survival rate in such patients. 24 It is obvious that more animal studies are necessary with different doses in order to determine the optimal dose to prevent oral cancers, paving the way for human studies.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, HESA-A is able to completely inhibit the growth of cells at the highest concentration of 5.4 mg/mL, whereas, at minor concentrations its effect is somewhat lower. Nevertheless, this mixture does not affect non tumoral cells and acts by following an apoptotic mechanism [178].…”
Section: Anticancer Activities Of Apium Plantsmentioning
confidence: 99%
“…HESA-A is a natural compound of herbal-marine origin which contains inorganic, organic and aqueous fractions with a wide range of therapeutic applications [4,17,18]. In this study, the interaction between HESA-A and influenza virus A/H1N1 was evaluated.…”
Section: Discussionmentioning
confidence: 99%